Intergenomic interactions between mitochondrial and Y-linked genes shape male mating patterns and fertility in Drosophila melanogaster. (1st November 2015) - Yee, Winston K.W.; Rogell, Björn; Lemos, Bernardo; Dowling, Damian K.
Abstract: Under maternal inheritance, mitochondrial genomes are prone to accumulate mutations that exhibit male-biased effects. Such mutations should, however, place selection on the nuclear genome for modifier adaptations that mitigate mitochondrial-incurred male harm. One gene region that might harbor such modifiers is the Y-chromosome, given the abundance of Y-linked variation for male fertility, and because Y-linked modifiers would not exert antagonistic effects in females because they would be found only in males. Recent studies in Drosophila revealed a set of nuclear genes whose expression is sensitive to allelic variation among mtDNA- and Y-haplotypes, suggesting these genes might be entwined in evolutionary conflict between mtDNA and Y. Here, we test whether genetic variation across mtDNA and Y haplotypes, sourced from three disjunct populations, interacts to affect male mating patterns and fertility across 10 days of early life in D. melanogaster . We also investigate whether coevolved mito-Y combinations outperform their evolutionarily novel counterparts, as predicted if the interacting Y-linked variance is comprised of modifier adaptations. Although we found no evidence that coevolved mito-Y combinations outperformed their novel counterparts, interactions between mtDNA and Y-chromosomes affected male mating patterns. These interactions were dependent on male age; thus male reproductive success was shaped by G × G × E interactions.